FACTORS THAT AFFECT BROILER PRODUCTION - Baracho, M. dos S.; Nääs, I. de A.; de Moura, D. J.; Lima, N. D. da S.; Cordeiro, A. F.; T.R. da Silva, R. Baracat (Revista Brasileira de Engenharia de Biossistemas, 2017)
Brazil occupies a privileged position worldwide in poultry farming. The economic activity is recognized as necessary for the country's GDP and also has a significant climatic diversity. Because of this, different types of aviaries were and still are built in the national territory. The objective of this study was to present a systematic review of the factors that have an impact on the intensive production of broiler chicken based on the scientific publications since the year 2000. The literature review showed a constant evolution and the knowledge about the form of housing that best expresses the genetics of birds. It was found that the thermal environment, air quality and other factors related to the housing of broiler chickens significantly imply in their performance.